An evaluation of Hospice New Zealand's interprofessional fundamentals of palliative care program at a single site. Issue 3 (23rd May 2014) - Henning, Marcus; Hu, Julie; Webster, Craig; Brown, Hadley; Murphy, Jo
Abstract: Objective: To study the efficacy of two modules within the Fundamentals of Palliative Care educational program within a single site. The modules included the concepts of Essence of Palliative Care and Pain and Symptom Management . Method: A mixed-methods approach incorporating questionnaires and interviews was implemented. Two phases were included. First, a purposive sample of 22 workshop participants were invited to fill out evaluation questionnaires on two occasions (immediately after the session and four weeks as follow-up). Second, semistructured interviews were conducted and interviews transcribed and analyzed using content analysis. Results: Participants felt they gained further knowledge in palliative patient management and refined their clinical practice. The questionnaire feedback revealed that the Essence of Palliative Care module provided a breadth of content but had difficulties in capturing the diverse needs of all attendees. The Pain and Symptom Management module was perceived as more technical and clinical, and this suited health professionals with an informed background. The interviewee feedback (three nurses, three nurse educators, one manager) suggested that the learning outcomes were comprehensive but needed to be more sensitive to learner needs. The teaching and learning activities were perceived as useful and encouraging. However, learners came from diverse contexts, and it was difficult to suit all learning preferences. Assessment and evaluation processes required more psychometric attention. Significance of Results: The piloting of the Fundamentals of Palliative Care program at this single site was of benefit and relevance to participants in their clinical practice. Overall, participants felt the course was useful to them and that they were able to gain valuable knowledge and skills. Several areas could be refined to optimize the learning, including: (1) knowing attendee learning potentialities and prior experiences, (2) considering a more inclusive and formal assessment process, (3) creating diverse mechanisms for disseminating knowledge and skills, and (4) improving methods of evaluation.